Association between dental agenesis and delay in dental development: a preliminary study in a Spanish paediatric population in relation with Dental Anomaly Pattern (DAP - León Rubio, Carmen; Martin Vacas, Andrea; Saavedra Marbán, Gloria; Paz Cortés, Marta Macarena (My University, 2024)
Background: The association between dental anomalies has been studied, giving rise to the concept of Dental Anomaly Pattern (DAP). Tooth agenesis has been associated with alterations such as molar infracclusion, taurodontism and delayed dental development. The aim of this study was to evaluate the dental development pattern in patients with non-syndromic dental agenesis, in comparison with a control group. Methods: Dental and chronological age was analysed in a sample size of 204 orthopantomographs divided into a study group (n=104) and a control group (n=100) with the Demirjian Method. Intra and intergroup diferences in chronological and dental age, and the correlation between them were calculated by statistical analysis with a 95% confdence level (p<0.05). Results: Dental age exceeded chronological age both in the control group and in the study group. Statistically signif¿ icant diferences (p=0.004) were found when comparing the diference between chronological and dental age in the study (-0.16±1.12) and control group (-0.58±0.90). Regarding sex and age intergroup diferences, the results were only statistically signifcant in the girls¿ group (p=0.017), and the age over 8 years old (p<0.05). There were no signif¿ cant diferences in tooth development depending on the number of missing teeth or the afected tooth group, but there was a delay in the development of the homologous tooth contralateral to the absent one in 14.9% of patients. Conclusions: The diference between chronological and dental age in permanent dentition is signifcantly lower in Spanish children with non-syndromic agenesis compared to a control group, presenting a lower dental age than chronological age than children without non-syndromic agenesis. Keywords: Dental anomaly pattern, DAP, Dental agenesis, Dental development, Paediatric dentistry, Childre